Republic of Tajikistan : Sixth Review Under the Three-Year Arrangement Under the Extended Credit Facility: Staff Report; and Press Release. (IMF Staff Country Reports; Country Report ;, 2012)
This paper presents key findings of the Sixth Review for Tajikistan under the Extended Credit Facility. Real GDP growth for 2011 reached 7.4 percent, driven mainly by agriculture, construction, and services. The authorities plan to maintain a conservative fiscal stance in line with the macroeconomic framework agreed during recent reviews, targeting a deficit of 0.5 percent of GDP. The fiscal stance for 2012 remains appropriate, but further consolidation will be necessary over the medium term to maintain fiscal and external sustainability.